1994
DOI: 10.1063/1.113069
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopic study of rubbed polyimide films

Abstract: Rubbed polyimide films have been studied by atomic force microscopy from micrometer to nanometer scales. On a large scale, oriented scratches and microstructures due to rubbing have been observed, while on a nanometer scale, oriented polyimide aggregates are visible. The alignment of liquid crystals on these films is thus discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…This phenomenon has been proposed previously to be induced by microgrooves (namely, scratches) generated during rubbing of the film surface. [1][2][3] However, some of the recent publications have suggested that the orientation of polymer chains near the film surface, which are generated by rubbing, plays a key role in aligning LCs at the surface. 4 -11 Others have proposed that both mechanisms are operative together.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been proposed previously to be induced by microgrooves (namely, scratches) generated during rubbing of the film surface. [1][2][3] However, some of the recent publications have suggested that the orientation of polymer chains near the film surface, which are generated by rubbing, plays a key role in aligning LCs at the surface. 4 -11 Others have proposed that both mechanisms are operative together.…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpretation of atomic resolution AFM images depends critically on the details of the tip-sample interaction [25]. AFM can reveal an image of a rubbed PI film surface, but the resolution is often not sufficient to resolve a single polymer chain [26]. Most of the topographic images of surfaces with adsorbed organic molecules collected with the AFM have been recorded in the contact mode.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, many alignment methods have been proposed to obtain the uniform alignment of LCs [1][2][3][4]. Among these methods, rubbing method is the most widely used and provides the superior electro-optical performance of LC switching [5,6]. However, contact type alignment method causes the electrostatic charges and mechanical damages so that deterioration of the image quality can occur.…”
Section: Introductionmentioning
confidence: 98%